English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
1

Hey,

I've got a que about this:
log(sub)2 (-x - 3) - log(sub)2 (x - 1) - log(sub)2(x + 3) = 1

I did this first -

log(sub)2 [(-x - 3) / (x - 1) / (x + 3)] = 1

and then i just cant figure out.
All suggestions greatly appriciated.

2007-06-10 08:13:51 · 5 answers · asked by jill b 1 in Science & Mathematics Mathematics

5 answers

You may use this:

log(sub)2 [(-x - 3) / (x - 1) / (x + 3)] = 1
2^[log(sub)2 [(-x - 3) / (x - 1) / (x + 3)] ]= 2^[1]
(-x - 3) /[(x - 1)(x + 3)] = 2
(-x-3) = 2(x - 1)(x + 3)

The rest it's all yours...

2007-06-10 08:22:13 · answer #1 · answered by Don Danielo 2 · 0 0

In the following,"log" means log to base 2:-
log(-x - 3) - log(x - 1) - log(x + 3) = 1
(-x - 3) / ((x - 1).(x + 3)) = 2
(-x - 3) = 2.(x - 1).(x + 3)
(-x - 3) = 2.(x² + 2x - 3)
2x² + 5x - 3 = 0
(2x - 1).(x + 3) = 0
x = 1/2 , x = - 3

2007-06-10 19:50:04 · answer #2 · answered by Como 7 · 0 0

It is really log(sub)2[(-x-3)/[(x-1)(x+3)] =1

reduce; log(sub)2[-1/(x-1)] =1
2^1 = -1/(x-1)
2(x-1) = -1
2x - 2= -1
2x = 1
x = 1/2

2007-06-10 08:25:08 · answer #3 · answered by teacher2006 3 · 0 0

OK that looks nearly correct. What you need is

log(sub)2[(-x-3)/((x-1)*(x+3))

Add logarithms to multiply numbers.

2007-06-10 08:24:19 · answer #4 · answered by PAUL W 2 · 1 0

You got a test tomorrow too,sorry i cant help,I only got 30percent in my last one.

2007-06-10 08:22:35 · answer #5 · answered by Julie 5 · 0 1

fedest.com, questions and answers